2021
DOI: 10.1007/s12070-021-02574-0
|View full text |Cite
|
Sign up to set email alerts
|

Title of the Article: Paranasal Mucormycosis in COVID-19 Patient

Abstract: There have been a variety of complications reported during and post- COVID infection. Recently, there has been an increase in sporadic cases of paranasal sinus mucormycosis in COVID- 19 patients. We report a case of COVID- 19 patient diagnosed to have orbital apex syndrome secondary to mucormycosis of nose and paranasal sinus requiring emergency endoscopic sinus surgery. Appropriate use of personal protective equipment and safety precautions taken by health care workers prevented the spread of the virus during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 12 publications
3
50
0
Order By: Relevance
“…The true incidence of rhino-orbital mucormycosis in COVID-19 patients is not known. However, there are multiple case reports describing mucormycosis in COVID-19 and most of these case reports are presently from India, especially in COVID-19 treated and recovered patients those were diabetic and corticosteroids were administered injudiciously for controlling severity of COVID-19, leading to a higher fatality in such cases and complicating the pandemic scenario [ 17 , 18 , 24 37 ].…”
Section: Incidence and Prevalencementioning
confidence: 99%
See 4 more Smart Citations
“…The true incidence of rhino-orbital mucormycosis in COVID-19 patients is not known. However, there are multiple case reports describing mucormycosis in COVID-19 and most of these case reports are presently from India, especially in COVID-19 treated and recovered patients those were diabetic and corticosteroids were administered injudiciously for controlling severity of COVID-19, leading to a higher fatality in such cases and complicating the pandemic scenario [ 17 , 18 , 24 37 ].…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Literature review identified 30 publications of case reports and case series of mucormycosis among COVID-19 patients [ 24 26 , 30 , 31 , 33 37 , 40 55 ]. Of all the reports, 11 publications were from India [ 24 26 , 30 37 ].…”
Section: Clinical Features and Managementmentioning
confidence: 99%
See 3 more Smart Citations